A REVIEW OF CONFLICT MANAGEMENT TECHNIQUES IN PROJECTS - Sudhakar, Goparaju Purna (Brazilian Journal of Operations & Production Management, 2015)
This paper finds the mostly occurring reasons for conflicts in projects and mostly used techniques to resolve the conflicts. Proposed a model of conflict management for projects. Total 105 reasons for conflicts in projects are identified from secondary research. From that top-10 reasons for conflicts in projects are founds based on number of references in the literature. They include Shared/Common Resources, Differences in Project Goal/Objective, Cultural Differences, Values Differences, Personality Issues, Differences in Technical Opinions/Approaches, Schedules, Costs, Administrative procedures, and Different Perceptions in the order of preference. Total 40 conflict resolution techniques in projects are identified based on through literature review. The most frequently used top -5 conflict resolution techniques in projects in the order of preference are Avoiding/Withdrawal, Compromising, Confronting/Problem Solving, Accommodating and Smoothing.